Switched Control Design for Nonlinear Systems Using State Feedback - Elias, Leandro J.; Faria, Flávio A. [UNESP]; Magossi, Rafael F. Q.; Oliveira, Vilma A. (Springer Nature, 2022)
In this work, a state feedback design for a class of continuous-time nonlinear systems is proposed. The nonlinear system is described by a Takagi–Sugeno fuzzy model and the stability conditions are ensured with a switched polynomial Lyapunov-like function. The state feedback design is based on a switched parallel distributed compensation (PDC) controller which avoids chattering/Zeno effects. Numerical examples illustrate the efficiency of the stabilizing conditions.
Keywords: PDC control; State feedback design; Switched polynomial Lyapunov-like function; TS fuzzy systems